Crosstalk between Wnt/β-catenin signaling pathway and DNA damage response in cancer: a new direction for overcoming therapy resistance - Zhang, Xixia; Yu, Xiaofeng (Frontiers in Pharmacology, 2023)
Wnt signaling plays an important role in regulating the biological behavior of cancers, and many drugs targeting this signaling have been developed. Recently, a series of research have revealed that Wnt signaling could regulate the DNA damage response (DDR), which is crucial for maintaining the genomic integrity in cells, and closely related to cancer genome instability. Many drugs have been developed to target the DDR in cancers. Notably, different components of the Wnt and DDR pathways are involved in crosstalk, forming a complex regulatory network and providing new opportunities for cancer therapy. Here, we provide a brief overview of Wnt signaling and the DDR in cancer research field and review the interactions between these two pathways. Finally, we also discuss the possibility of therapeutic agents targeting Wnt and DDR as potential cancer treatment strategies.